Influências da produção textual científica na formação de estudantes universitários - Menezes, Talita Santos (2015)
One of the aims of undergraduate courses is to stimulate undergraduate students to get a critical spirit. So, the activities which were done during the course cooperate, anyhow, to reach this aim and the textual production makes part of this group of tasks. According to this, the scientific textual production acquires goals which go beyond their didactic evaluative function, contributing to the student's knowledge development. Based on this perspective, the aim of this study is to analyze how the scientific textual production can develop, critically, the way the undergraduate students think. The theoretical reference which supported the arguments was based, fundamentally, on conceptions hold by Koch (2006;2012), Silva (2012), Hühne (2001), Chauí (2001), Garcia (2001), among others. The corpus analysed was made of a group of 106 texts produced by undergraduate students and 20 recorded interviews with professors and university students. From the analysis of data, it was possible to verify how the scientific textual production influences the undergraduate students' critical positioning in some issues, wherein this positioning is revealed by the argumentation found in the textual materiality.